Influence of Combined Application of Inorganic N and P Fertilizers and Chicken Manure on Quality and Shelf-Life of Garlic (Allium sativum L.) Bulbs - Shiferaw, G Diriba; Dechassa, R Nigussie; Kebede, Woldetsadik; Getachew, Tabor; Sharma, J J (Journal of Postharvest Technology, 2016)
Crop quality and shelf-life improvement with soil fertility maintenance requires a balanced application of inorganic and organic nutrient sources. Thus, a field experiment was conducted to investigate the effect of chicken manure (CM) combined with reduced levels of nitrogen and phosphorus fertilizers on garlic quality and shelf-life at Debre Zeit Agricultural Research Centre, Ethiopia, on two soil types (Andosols and Vertisols). The treatments consisted of factorial combinations of three levels of nitrogen (0, 46 and 92 kg N /ha), three levels of phosphorus (0, 20 and 40 kg P /ha) and three levels of chicken manure (0, 10 and 20 t CM /ha). The treatments were laid out in a randomized complete block design with three replications at each soil type. Results showed that the main effects of nitrogen, phosphorus, chicken manure and soil type had a positive and significant effect on the evaluated quality parameters in the experiments. The effect of the manure on shelf-life and qualities of garlic bulb were significantly higher in both soils than the mineral N and P fertilizers, but the highest quality of garlic bulb was recorded on Vertisols than on Andosols. The interactions of the appliedQuality, shelf life and mineral contents of garlic bulbs were significantly influenced by the interaction effect of fertilizers; the better values being obtained with the combined application of 46 kg N /ha, 20 kg P /ha and 20 t CM /ha on both soils. However, the highest bulb qualities were obtained in the combined application of 46 kg N, 20 kg P and 10 t CM /ha on Andosols. Thus, application of 10 or 20 t /ha CM resulted in a saving of 50% of the recommended levels of both inorganic N and P fertilizers, without reducing the bulb quality of garlic. fertilizers also significantly influenced the quality traits of garlic on both soils